Early and unrestricted access to high-efficacy disease-modifying therapies: a consensus to optimize benefits for people living with multiple sclerosis - Filippi, Massimo; Danesi, Romano; Derfuss, Tobias; Duddy, Martin; Gallo, Paolo; Gold, Ralf; Havrdová, Eva Kubala; Kornek, Barbara; Saccà, Francesco; Tintoré, Mar; Weber, Jörg; Trojano, Maria (Journal of neurology, 2022)
Early intervention with high-efficacy disease-modifying therapy (HE DMT) may be the best strategy to delay irreversible neurological damage and progression of multiple sclerosis (MS). In European healthcare systems, however, patient access to HE DMTs in MS is often restricted to later stages of the disease due to restrictions in reimbursement despite broader regulatory labels. Although not every patient should be treated with HE DMTs at the initial stages of the disease, early and unrestricted access to HE DMTs with a positive benefit–risk profile and a reasonable value proposition will provide the freedom of choice for an appropriate treatment based on a shared decision between expert physicians and patients. This will further optimize outcomes and facilitate efficient resource allocation and sustainability in healthcare systems and society.